Análisis de impacto del clima organizacional en los almacenes de cadena. caso estudio: Súper Tiendas el Imperio Sede Buenaventura (2023)
The work climate is a crucial factor that can have a significant impact on the effectiveness, contentment, and involvement of employees in a company. Therefore, it is essential to carry out an analysis of how the work environment is affecting the employees in the warehouses of the chain stores. One of the specific objectives is to evaluate the current situation of the work environment in the Buenaventura branch of Supertienda El Imperio.